Червона армія очима львів’ян восени 1939 р. - Мрака, І.Б. (Український історичний журнал, 2016)
На основі джерел особового походження (спогади, щоденники), архівних документів, публікацій у пресі та праць істориків зроблено спробу розглянути життя Львова напередодні вступу Червоної армії, оцінку радянських військовиків
львів’янами. Описано сприйняття мешканцями міста червоноармійців, їхню
поведінку. Відображено також бачення вересневих подій представниками «країни Рад». September 1939 was a turning point for the city of L’viv and its inhabitants. The article
describes the living atmosphere of the city and its inhabitants before and at the
time of Red Army invasion. The author analyzed and described L’vіv’s perception of soviet
troops and their behaviour in the city and in the homes of its citizens. Being based
on archival sources the article also reflects the Red Army representatives’ vision of the
September events in L’viv.